Strategy to increase the number of halal self-declared certification in Indonesia - Aurahma, Adora; Arsyianti, Laily Dwi (IPB University, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are obtaining halal certification through self-declared halal certification. The utilization has not reached the maximum potential even though this form of certification is available in Indonesia. Out of 349,834 free halal self-declared certification offered by the government, only 119,662 have been used (BPJPH 2022). Despite the benefits, there are several issues related to the implementation. Only a small percentage of MSMEs have obtained halal certification in developing a strategy to address the issue. Therefore, this research aimed to identify strengths, weaknesses, opportunities, and threats (SWOT) associated with self-declared halal certification as well as propose strategy to increase the use from a stakeholder perspective. SWOT analysis was used to evaluate the potential development strategies of self-declared stakeholders, such as Indonesian Ulema Council (MUI), Halal Product Process (PPH) Assistants, and Halal Product Guarantee Organization (BPJPH). Meanwhile, Analytic Network Process (ANP) method prioritized the four aspects and determined the best strategy for developing halal self-declaration policies. An assertive strategy providing fair information dissemination and optimizing support for PPH assistants was needed to address the issue of low self-declared certification. Based on this research, the government provided a reasonable honorarium for PPH assistants. BPJPH used AI and blockchain technologies to expedite the document collection process for MSMEs and PPH assistants. Additionally, PPH adopted more proactive and creative methods for assistance.